THE PREVALENCE OF RISK FACTORS FOR CHRONIC NON-COMMUNICABLE DISEASES IN STUDENT POPULATION - O. S. Kobyakova; I. A. Deev; A. M. Lukashova; E. A. Starovoytova; E. S. Kulikov (Кардиоваскулярная терапия и профилактика, 2016)
The review focuses on the results of epidemiological and clinical trials, which witness high prevalence of risk factors for chronic noncommunicable diseases in student population, their common combination and potentiating negative impact on the health and academic success of students. The results of literature data analysis underlies an aim for further long-term population epidemiologic studies, trends and age tracking of the main risk factors for chronic noncommunicable diseases in student population, with properly organized interinstitutional system of medical-social follow-up of the studying and research for differentiated prevention technologies.